2020
DOI: 10.1001/jamasurg.2019.4539
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Postoperative Infection With Risk of Long-term Infection and Mortality

Abstract: IMPORTANCE Surgical site infection has been shown to decrease survival in veterans by up to 42%. The association of 30-day postoperative infections with long-term infections in the overall surgical population remains unknown.OBJECTIVE To determine whether exposure to 30-day postoperative infection is associated with increased incidence of infection and mortality during postoperative days 31 to 365. DESIGN, SETTING, AND PARTICIPANTS In this retrospective observational cohort study, veterans undergoing major sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
2
34
0
3
Order By: Relevance
“…Moreover, SSI is an important risk factor for readmission, reintervention, and the development of incisional hernia [4,5], resulting in increased healthcare-related costs [6]. Postoperative infectious complications also negatively affect long-term outcomes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SSI is an important risk factor for readmission, reintervention, and the development of incisional hernia [4,5], resulting in increased healthcare-related costs [6]. Postoperative infectious complications also negatively affect long-term outcomes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There were various SSI definitions across the studies we compared our results to seven studies reported their results by formally recognized diagnostic system such as the CDC definition or another validated definition [28].…”
Section: Discussionmentioning
confidence: 99%
“…Complications varied among age groups (Table 3). However, young age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) had no complications at all. Table 3 shows the distribution of complications among study participants according to age group.…”
Section: Surgery Complicationsmentioning
confidence: 99%
“…Em território brasileiro, entende-se que as infecções de sítio cirúrgico ocupam o terceiro lugar em infecções relacionadas à assistência à saúde, representando cerca de 14 a 16% dos quadros apresentados pelos pacientes internados (5)(6) . A ISC é associada a um aumento de mortalidade, além de prolongar o período de internação (7)(8) . Possui uma taxa de mortalidade média de 3%, destacando o fato de 75% das mortes de pacientes com infecção de sítio cirúrgico serem diretamente ligadas ao processo infeccioso como causa primária do óbito (9)(10) .…”
Section: Introductionunclassified